Vestibular Rehabilitation for Peripheral Vestibular Hypofunction: An Evidence-Based Clinical Practice Guideline. Issue 2 (April 2016) - Hall, Courtney D.; Herdman, Susan J.; Whitney, Susan L.; Cass, Stephen P.; Clendaniel, Richard A.; Fife, Terry D.; Furman, Joseph M.; Getchius, Thomas S. D.; Goebel, Joel A.; Shepard, Neil T.; Woodhouse, Sheelah N.
Abstract : Background: Uncompensated vestibular hypofunction results in postural instability, visual blurring with head movement, and subjective complaints of dizziness and/or imbalance. We sought to answer the question, "Is vestibular exercise effective at enhancing recovery of function in people with peripheral (unilateral or bilateral) vestibular hypofunction?" Methods: A systematic review of the literature was performed in 5 databases published after 1985 and 5 additional sources for relevant publications were searched. Article types included meta-analyses, systematic reviews, randomized controlled trials, cohort studies, case control series, and case series for human subjects, published in English. One hundred thirty-five articles were identified as relevant to this clinical practice guideline. Results/Discussion: Based on strong evidence and a preponderance of benefit over harm, clinicians should offer vestibular rehabilitation to persons with unilateral and bilateral vestibular hypofunction with impairments and functional limitations related to the vestibular deficit. Based on strong evidence and a preponderance of harm over benefit, clinicians should not include voluntary saccadic or smooth-pursuit eye movements in isolation (ie, without head movement) as specific exercises for gaze stability. Based on moderate evidence, clinicians may offer specific exercise techniques to target identified impairments or functional limitations. Based on moderate evidence and in consideration of patient preference, clinicians may provide supervised vestibular rehabilitation. Based on expert opinion extrapolated from the evidence, clinicians may prescribe a minimum of 3 times per day for the performance of gaze stability exercises as 1 component of a home exercise program. Based on expert opinion extrapolated from the evidence (range of supervised visits: 2-38 weeks, mean = 10 weeks), clinicians may consider providing adequate supervised vestibular rehabilitation sessions for the patient to understand the goals of the program and how to manage and progress themselves independently. As a general guide, persons without significant comorbidities that affect mobility and with acute or subacute unilateral vestibular hypofunction may need once a week supervised sessions for 2 to 3 weeks; persons with chronic unilateral vestibular hypofunction may need once a week sessions for 4 to 6 weeks; and persons with bilateral vestibular hypofunction may need once a week sessions for 8 to 12 weeks. In addition to supervised sessions, patients are provided a daily home exercise program. Disclaimer: These recommendations are intended as a guide for physical therapists and clinicians to optimize rehabilitation outcomes for persons with peripheral vestibular hypofunction undergoing vestibular rehabilitation. Video Abstract available for more insights from the author (see Video, Supplemental Digital Content 1, http://links.lww.com/JNPT/A124 ). Abstract : Supplemental Digital Content is Available in the Text.